Managing Information Systems Ten Essential Topics - Xu, Jun.; Quaddus, Mohammed; SpringerLink (Online service) (Paris : Atlantis Press : Imprint: Atlantis Press, 2013)
Information systems (IS)/Information technology(IT) has become an essential part and a major resource of the organization. IS/IT is a major resource that can radically affect the structure of an organisation, the way it serves customers, and the way it helps people in organisations to communicate both internally and externally, and the way an organisation runs its business. Managing information and information systems effectively and efficiently have become an essential part of the life of 21st century managers. This book is about Managing information and information systems and focuses on relationships between information, information systems/information technology, people and business. The impacts, roles, risks, challenges as well as emerging trends of information systems will be an important element of the book. At the same time, many strategic and contemporary uses of information systems such as implementing enterprise planning systems for improving internal operation, adopting customer relationship management systems and supply chain management systems to enhance relations with customers and suppliers/partners respectively, and establishing knowledge management systems for better managing organizational knowledge resources as well as using different information systems for supporting managers$1 (Bdecision making in all levels will be an integral part of the book. In addition, essential and critical information systems management skills including using information systems for competitive advantages, planning and evaluating information systems, system development & implementing information systems, and managing information systems operations will be a critical part of the book.s
Foundation -- Information Systems for Competitive Advantages -- Information Systems Planning and Evaluation -- Developing and Implementing Information Systems -- Managing Organization$1 (Bs Knowledge Resources -- Managing Infrastructure for Information Systems -- Using Information Systems for Enhancing Internal Operation -- Using Information Systems for Improving External Relations -- Using Information Systems for Supporting Decision Making -- Information Systems Operation Management.s
Keywords: Economics; Management information systems; Economics/Management Science; Economics/Management Science, general; Business Information Systems; Innovation/Technology Management